Barriers the Application of Modern Education Technology in the First Cycle of the Basic Education Schools in Lattakia City from the Schools' Teachers point of view - A Field Study - خيرات جبلاوي, رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aim to expose the Barriers the Application of Modern Education Technology in the First Cycle of the Basic Education Schools in Lattakia City from the Schools' Teachers point of view. To achieve the object of the research a questionnaire has been included (48) paragraphs, divided into four main axes: (teacher-related obstacles, administration related obstacles, infrastructure and equipment-relate obstacles, student-related obstacles). then applied to a sample of (288) teacher in first Cycle of Basic Education Schools in Lattakia city for the academic year 2018/2019. The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (11) of the teaching staff of educational at Tishreen and Tartous universities. Pilot sample consisted of (36) Teachers, Reliability was established by Cronbach – Alpha Reliability at least (0.726), and (0.971) in Spearman, Brown, which indicate to high reliability to questionnaire. The research ended up with the following results: The Barriers the Application of Modern Education Technology in the First Cycle of the Basic Education Schools in Lattakia City from the Schools' Teachers point of view was middle degree. No statistically significant differences regarding with the Barriers the Application of Modern Education Technology in the First Cycle of the Basic Education Schools in Lattakia City according to variable (experience). There are statistically significant differences regarding with the Barriers the Application of Modern Education Technology in the First Cycle of the Basic Education Schools in Lattakia City according to variables (educational qualification in favor of the Education Preparation Diploma Teachers, and to training courses in favor of the follow the training courses). The researcher advice that the training courses held by the Ministry of Education be evaluated and the infrastructure and its equipment be improved.